Quality Control and Cost Control Analysis of Pulmonary Tuberculosis Clinical Pathway - Salyanti Puji Negeri; Ratno Adrianto; Irfansyah Baharuddin Pakki (Indonesian Journal of Global Health Research, 2025)
Tuberculosis is one of the global health issues discussed at the G20 meeting in 2020 in Indonesia, where the number of pulmonary tuberculosis patients in Indonesia continues to increase, where the treatment of pulmonary tuberculosis patients in hospitals requires clinical pathways to provide effective and efficient services to pulmonary tuberculosis patients in the treatment room. The study was conducted quantitatively with a cross sectional research design conducted on 127 medical record files of pulmonary tuberculosis patients in the inpatient treatment room at RSUD IA Moeis Samarinda in 2024 using purposive sampling. Electronic instruments of patient medical records were used to obtain data on compliance with specialist visits, laboratory examinations, thoracic X-ray examinations, administration of Anti-Tuberculosis Drugs, Length of stay, Cost of Drugs and Consumables (BHP), and Cost of Services to assess the effect of Quality Control and Cost Control of Clinical pathway for pulmonary tuberculosis patients hospitalized at RSUD IA Moeis Samarinda. Multivariate analysis using Kruskal Walls test. The results showed that variables that had an influence on the clinical pathway included compliance with specialist visits, where an increase in compliance with specialist visits was also obtained in the group without clinical pathway on average 57.04%, and the group with clinical pathway amounted to 64.07%. Antituberculosis drug administration also increased, in the group without clinical pathway by 22.6% and in the group with clinical pathway by 44.2%. Other variables that also affect the clinical pathway are Length of stay, Cost of Drugs and BHP, and Cost of Services. While 2 other variables, laboratory examination and radiology examination, did not affect the clinical pathway. The conclusion of this study is that clinical pathway is significantly related to visit compliance, OAT administration, Length of Stay, BHP Costs and Service Costs.